Preparation and characterization of hydrogels from carboxymethyl cellulose and 1-vinyl-2-pyrrolidone using irradiation techniques for slow release application - Mohd Yazid, Norhanifah (2011)
Hydrogels from carboxymethyl cellulose (CMC) and 1-vinyl-2-pyyrolidone (VP) were prepared via electron beam and ultraviolet radiations. Optimization of the preparation parameters was carried out for both methods where the optimum stirring time and percentage of crosslinking agents were at 3 hour of stirring and 5 % of BIS respectively. The hydrogels were prepared by irradiating CMC/VP samples with electron beam at 5, 10, 15, 20 and 25 kGy irradiation doses. For ultraviolet radiation, the optimum irradiation time and percentage of photoinitiator were at 8 hour of exposure and 1 % of photoinitiator. The effect of electron beam dose and concentrations of CMC on gel fraction, swelling behaviour, thermal properties and surface morphology were studied. When the irradiation dose and the concentration of CMC were increased, the gel fraction increased. Increasing the irradiation dose or the concentration of CMC resulted in the decrease of degree of swelling. The highest degree of swelling was obtained in alkaline medium followed by distilled water, salt and acidic media. In the temperature-swelling studies, the highest degree of swelling was recorded at room temperature (25 oC). The FTIR analysis showed there was a intermolecular interaction between C=O and O-H which could be due to the intermolecular hydrogen bonding of carboxylic group and non-substituted hydroxyl groups in the CMC. Thermogravimetric analysis and differential thermogravimetric of hydrogels showed that thermal stability of hydrogels increased with increasing irradiation dose, but decreased when the concentration of CMC was increased. Differential scanning spectroscopy thermograms showed that melting temperature of hydrogels was affected by irradiation dose and concentration of CMC. The surface morphology study showed the pore size of the hydrogels was dependent on irradiation dose and concentration of CMC which affected the crosslinking density of the hydrogels. For the controlled release study, the highest released obtained from hydrogels irradiated at 10 kGy. For the ultraviolet radiation study, the gel fraction obtained was less than electron beam radiation and the degree swelling of hydrogels decreased with increasing gel fraction. The thermal properties showed that the melting temperatures of the hydrogels decreased compared to pure CMC and VP. The surface morphology study showed the pores size obtained after ultraviolet radiation was heterogeneous. Overall analysis revealed that electron beam radiation was the better technique compared to the ultraviolet radiation for preparing CMC/VP hydrogels.